"But what story?": a narrative-discursive analysis of "white" Afrikaners' accounts of male involvement in parenthood decision-making - Morison, Tracy (Rhodes University, Faculty of Humanities, Department of Psychology, 2011)
Despite the increased focus on men in reproductive research, little is known about male involvement in the initial decision/s regarding parenthood (i.e., to become a parent or not) and the subsequent decision-making that may ensue (e.g., choices about timing or spacing of births). In particular, the parenthood decision-making of "White" , heterosexual men from the middle class has been understudied, as indicated in the existing literature. In South Africa, this oversight has been exacerbated by the tendency for researchers to concentrate on "problematic" men, to the exclusion of the "boring, normal case" . I argue that this silence in the literature is a result of the taken for granted nature of parenthood in the "normal" heterosexual life course. In this study, I have turned the spotlight onto the norm of "Whiteness" and heterosexuality by studying those who have previously been overlooked by researchers. I focus on "White" Afrikaans men's involvement in parenthood decision-making. My aim was to explore how constructions of gender inform male involvement in decision-making, especially within the South African context where social transformation has challenged traditional conceptions of male selfhood giving rise to new and contested masculine identities and new discourses of manhood and fatherhood. In an effort to ensure that women's voices are not marginalised in the research, as is often the case in studies of men and masculinity, I conducted in-depth, semi-structured interviews about male involvement in decision-making with both "White" Afrikaans women and men. There were 23 participants in total, who all identified as heterosexual and middle-class. The participants were divided into two age cohorts (21 "“ 30 years and >40 years), which were then differentiated according to gender, reproductive status, and relationship status. Treating the interviews as jointly produced narratives, I analysed them by means of a performativity/performance lens. This dual analytic lens focuses on how particular narrative performances are simultaneously shaped by the interview setting and the broader discursive context. The lens was fashioned by synthesising Butler's theory of performativity with Taylor's narrative-discursive method. This syn
Keywords: Family planning -- South Africa -- Psychological aspects; Family size; Birth intervals; Men -- South Africa -- Attitudes; Men -- South Africa -- Psychology; Couples -- South Africa -- Psychology; Afrikaners -- Attitudes